IDENTIFICATION OF COPING STRATEGIES FOR COVID-19 INFECTED PATIENTS RELATED TO MENTAL HEALTH CHALLENGES DURING THE QUARANTINE PERIOD IN PUNJAB, PAKISTAN: A QUALITATIVE APPROACH - Gulnaz Banu; Tikka Khan Faisal; Shamim Akhtar; Zahida Abbas; Gulzareen (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: The COVID-19 pandemic has presented unprecedented mental health challenges for infected patients during the quarantine period, necessitating the identification of effective coping strategies to mitigate the psychological impacts of social isolation, fear, and uncertainty.Objective: To identify the coping strategies for COVID-19 infected patients related to mental health challenges during the quarantine period in Punjab, Pakistan.Methods: A qualitative exploratory phenomenological approach was employed to gather data from confirmed COVID-19 cases who met the inclusion and exclusion criteria and were undergoing quarantine. Semi-structured interviews were conducted in person, recorded, and subsequently transcribed. The transcripts were then subjected to thematic analysis to identify patterns and themes. This method allowed for an in-depth examination of participants' experiences and perceptions, providing rich and detailed insights into their coping strategies and mental health challenges during quarantine.Results: Patients hospitalized with COVID-19 identified family emotional support as a crucial factor in their ability to cope with the illness, with loved ones providing encouragement and strength. The care and support from medical staff also played a vital role in giving patients a sense of security and empowerment. Many patients found solace in their spiritual beliefs, feeling protected and saved by their faith in God. Additionally, patients actively employed various coping strategies, including professional counseling, cognitive changes, and goal-setting, to psychologically adapt to their situation.Conclusion: Patients hospitalized with COVID-19 drew strength and resilience from a combination of family emotional support, medical staff care, spiritual beliefs, and personal coping strategies to navigate the challenges of their illness.